2020
DOI: 10.1016/j.cardfail.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling Associates with Disease Severity in Nonischemic Dilated Cardiomyopathy

Abstract: Background: Metabolomic profiling may have diagnostic and prognostic value in heart failure. This study investigated whether targeted blood and urine metabolomics reflects disease severity in patients with nonischemic dilated cardiomyopathy (DCM) and compared its incremental value on top of N-terminal prohormone of brain natriuretic peptide (NT-proBNP). Methods and Results: A total of 149 metabolites were measured in plasma and urine samples of 273 patients with DCM and with varying stages of disease (patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 39 publications
(53 reference statements)
1
30
0
Order By: Relevance
“…The development of high-throughput metabolomic technologies has allowed to investigate large patient cohorts of different disease states and to achieve new inputs for putative diagnostic, prognostic or therapy surveillance markers. Thus, independent studies previously reported metabolic alterations in the failing heart [25,31,32]. Aortic stenosis belongs to the most frequent clinical causes of hospitalization and mortality in elderly people and TAVR, being the preferred option for elderly patients, is a well-established interventional therapy for permanent improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The development of high-throughput metabolomic technologies has allowed to investigate large patient cohorts of different disease states and to achieve new inputs for putative diagnostic, prognostic or therapy surveillance markers. Thus, independent studies previously reported metabolic alterations in the failing heart [25,31,32]. Aortic stenosis belongs to the most frequent clinical causes of hospitalization and mortality in elderly people and TAVR, being the preferred option for elderly patients, is a well-established interventional therapy for permanent improvement.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study that implemented untargeted metabolomics analysis combined with ML algorithms in order to select metabolites creating the top performing diagnostic model for HFrEF. Recently, Verdonschot et al 18 www.nature.com/scientificreports www.nature.com/scientificreports/ have shown that the NT pro-BNP-based determination of the dilated cardiomyopathy (DCM) severity might be complemented by the combination of metabolites. In contrast to our study, authors have applied targeted metabolomics approach which might limit objective analysis of changes occurring in the blood/urine metabolites' profile.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found a greater level in early stage HFpEF relative to HFrEF; however, this may be due to discrepancies in HFrEF severity and cohort sizes ( Zordoky et al, 2015 ; Bedi et al, 2016 ). Significant circulating LCAC upregulation occurs in both ischemic and non-ischaemic HF etiologies, although the upregulation is significantly greater in ischaemic HF patients ( Lanfear et al, 2017 ; Verdonschot et al, 2019 ). Importantly, circulating LCAC levels were found to normalize to non-failing levels following left ventricular assist device implantation of aortic valve replacement ( Ahmad et al, 2016 ; Elmariah et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…LCACs are intermediates of intracellular fatty acid metabolism. High LCAC levels have been associated with key CVDs, including heart failure (HF), coronary artery disease (CAD), and cardiac arrhythmias ( Shah et al, 2010 ; Kalim et al, 2013 ; Rizza et al, 2014 ; Zordoky et al, 2015 ; Krause et al, 2018 ; Verdonschot et al, 2019 ). Moreover, the LCAC-CVD association has been reported to be proportional to disease severity in many studies ( Lai et al, 2014 ; Ahmad et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation